1998
DOI: 10.1002/(sici)1521-396x(199804)166:2<659::aid-pssa659>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Grain Growth during the Laser Interference Crystallization of a-Si

Abstract: We used laser interference (LIC), a combination of pulsed laser crystallization and holography, to fabricate polycrystalline silicon lines in an amorphous silicon (a‐Si) film. Under appropriate conditions, the grains in the lines reach in‐plane dimensions appreciably larger than the thickness of the initial a‐Si film (up to 1.7 μm for a 300 nm a‐Si film). Atomic force and transmission electron microscopy indicate that these large grains result from the lateral solidification of the silicon lines melted by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The width of 7 ns of the Nd:YAG pulses is shorter than those of over 20 ns of conventional excimer lasers. 13 The structural properties of the crystallized samples were investigated using cross-sectional TEM and Raman spectroscopy. 4,12 The laser beam profile was homogenized using a vacuum spatial filter, leading to a Gaussian-like intensity profile with a diameter 0 ϭ4 mm on the sample surface.…”
Section: Methodsmentioning
confidence: 99%
“…The width of 7 ns of the Nd:YAG pulses is shorter than those of over 20 ns of conventional excimer lasers. 13 The structural properties of the crystallized samples were investigated using cross-sectional TEM and Raman spectroscopy. 4,12 The laser beam profile was homogenized using a vacuum spatial filter, leading to a Gaussian-like intensity profile with a diameter 0 ϭ4 mm on the sample surface.…”
Section: Methodsmentioning
confidence: 99%
“…This technique has been successfully utilized to change the structure of the various amorphous materials (carbon nitride (Zhang and Nakayama, 1997) or amorphous silicon (Aichmayr et al, 1998)). Thin films of various SiO x compositions have been irradiated with different fluxes of UV laser photons (λ=274 nm).…”
Section: Phase Separation Induced By Uv Photons Irradiationmentioning
confidence: 99%
“…6 The lateral temperature gradient induced by the selective illumination has also been applied to induce a lateral solidification of amorphous silicon films, which permits the control of grain size and orientation of the crystallized material. 3,4,7,8 In a previous work, 9 we have demonstrated that amorphous ͑a-͒ Ge films deposited on crystalline GaAs substrates can be epitaxially crystallized when irradiated by short laser pulses. The Ge/GaAs system is ideal for laser crystallization studies since the two materials are almost perfectly matched with respect to lattice constants and thermal expansion coefficients.…”
Section: Introductionmentioning
confidence: 98%
“…LIC allows for the fabrication of periodic structures in a ns time scale without the need for lithography. It has been employed to fabricate arrays of lines or of dots of polycrystalline silicon [2][3][4] and polycrystalline germanium 5 on glass substrates as well as for the structuring of crystalline GaAs/͑Al,Ga͒As multilayers. 6 The lateral temperature gradient induced by the selective illumination has also been applied to induce a lateral solidification of amorphous silicon films, which permits the control of grain size and orientation of the crystallized material.…”
Section: Introductionmentioning
confidence: 99%